Closed-loop control for precision antimicrobial delivery: an In silico proof-of-concept - Herrero,P; Rawson,TM; Philip,A; Moore,LSP; Holmes,AH; Georgiou,P (IEEE Transactions on Biomedical Engineering, 2018)
IEEE Objective: Inappropriate dosing of patients with antibiotics is a driver of antimicrobial resistance, toxicity, and poor outcomes of therapy. In this paper, we investigate, in silico, the hypothesis that the use of a closed-loop control system could improve the attainment of pharmacokinetic-pharmacodynamic targets for antimicrobial therapy, where wide variations in target attainment have been reported. This includes patients in critical care, patients with renal disease and patients with obesity.